Galactorrhea in Breast Augmentation - Arellano, Aristides; Arellano-Montalvo, Fics-Anja; Arellano-Montalvo, Dafne (European Journal of Applied Sciences, 2023)
Augmentation mammoplasty is one of the most used procedures in breast surgery and its complications have been very well studied. However, periprosthetic galactocele after prosthetic breast augmentation surgery is a very little-known complication.